2012
DOI: 10.3920/bm2012.0021
|View full text |Cite
|
Sign up to set email alerts
|

Screening for lactic acid bacteria capable of inhibiting Campylobacter jejuni in in vitro simulations of the broiler chicken caecal environment

Abstract: Thermotolerant Campylobacter spp., specifically Campylobacter jejuni and Campylobacter coli, are the most common bacterial causes of human gastroenteritis in developed countries. Consumption of improperly prepared poultry products and cross contamination are among the main causes of human campylobacteriosis. The aim of this study was to identify lactic acid bacterial (LAB) strains capable of inhibiting C. jejuni growth in initial in vitro trials ('spot-on-lawn' method), as well as in batch fermentation studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…Whereas, in clinical settings with immune-compromised patients, E.faecalis can be considered an opportunistic pathogen [1], it has also been shown to impart beneficial effects to health. A recent in vitro study demonstrated that E. faecalis was inhibitory to C. jejuni MB 4185 infection under simulated broiler caecal condition [2]. An E.faecalis isolated from a healthy adult showed the highest probiotic activity when compared with over 70 other lactic acid bacteria (LAB) isolates, including lactobacilli and bifidobacteria [3].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, in clinical settings with immune-compromised patients, E.faecalis can be considered an opportunistic pathogen [1], it has also been shown to impart beneficial effects to health. A recent in vitro study demonstrated that E. faecalis was inhibitory to C. jejuni MB 4185 infection under simulated broiler caecal condition [2]. An E.faecalis isolated from a healthy adult showed the highest probiotic activity when compared with over 70 other lactic acid bacteria (LAB) isolates, including lactobacilli and bifidobacteria [3].…”
Section: Introductionmentioning
confidence: 99%
“…For example, there is little available information regarding the relationship between chytrid growth inhibition in vitro and effective inhibition of fungal growth or the development of disease in vivo. Experimental efforts using probiotics to control Campylobacter in poultry show that the relationship will probably not be straightforward and that some bacteria that are inhibitory are ineffective against pre-existing infections [37,38]. Efficient and persistent host and environmental colonization needs to be established: amphibian skin microbiomes are dynamic and can be unstable and unpredictable, and bacterial community composition changes over the animal's lifetime [32].…”
Section: Trialled and Testedmentioning
confidence: 99%
“…72 However, the treatment of cell-free supernatants from these strains with proteinase K or chymotrypsin did not affect this activity, suggesting that something other than bacteriocins (e.g., organic acids) may be responsible. 72 Following protease and heat studies, the anti-Campylobacter activity of a Lactobacillus reuteri isolate was deemed unlikely to result from the production of bacteriocins, instead possibly resulting from the production of reuterin (3-hydroxypropionaldehyde), an antimicrobial metabolite. 73 Apart from lactobacilli, the other LAB most commonly associated with anti-Campylobacter activity are Enterococcus faecium and Enterococcus faecalis.…”
Section: Antimicrobial Peptides Active Against C Jejuni From Labmentioning
confidence: 98%
“…73 As with some Lactobacillus spp., there is evidence that some enterococci exert antagonism towards C. jejuni through means other than bacteriocins. 72 The anti-Campylobacter activity of certain strains of E. faecium and Lactobacillus pentosus was enhanced through the action of cellulase, although the source of this activity is not characterized. 77 Lactobacillus spp.…”
Section: Antimicrobial Peptides Active Against C Jejuni From Labmentioning
confidence: 99%